RISK ASSESSMENT ON THE BRIDGE CONSTRUCTION PROJECT (CASE STUDY: BATANG JUJUAN AND BATANG GANEH BRIDGE CONSTRUCTION PROJECTS) - Zona, Hafizh
Implementing a bridge construction project in the West Sumatra region will likely create many risks that stakeholders must consider because the impact is detrimental and can affect the overall project completion. In this case, it is necessary to carry out risk analysis, determine risk priorities, and respond to risks concerning ISO 31000:2018. Starting from the first thing, namely knowing for sure the risks that arise from each stakeholder, the second is determining the risk parameters for each risk source using an analytical hierarchy process approach, and the third is knowing the risk response strategy of each stakeholder. To obtain accurate results in analyzing the risks of each stakeholder, several people represent each element of the stakeholders who are considered capable and have adequate knowledge about the risks that will occur during the implementation of bridge construction in the West Sumatra region.